The impact of tobacco brands advertisements on television viewers / Gan Siew Yew - Gan , Siew Yew (1989)
This academic exercise is an attempt to study the impact of tobacco brands advertisements on television viewers. 50 respondents are used as samples for this study. Chapter one is an introduction to this research study. It contains the background of the tobacco brands advertisements, purposes of this study and the literature review. Chapter two deals with the research methods and problems encountered in Basically, the research methods are this study. observation and interview questionaire. Library research is also another method. In the third chapter, various aspects and topics concerning advertising are discussed. Firstly, a short history and introduction on advertising is given. Then, the way to make an advertisement and to create an impact is presented . Other aspects such as advertising in Malaysia and television advertising are also brought in. Lastly, included in this chapter are discussions about images and attitudes and the positive and negative effects of advertising. The core of this study is presented in Chapter Four. In this chapter presented and the data which has been collected is analysed. The advertisements are first categorised based on the observations and the responses of the respondents are later analysed and discussed. Lastly, Chapter Five rounds up this study by giving a general conclusion of the findings of this study.